EGFR Activation Impairs Antiviral Activity of Interferon Signaling in Brain Microvascular Endothelial Cells During Japanese Encephalitis Virus Infection - Zhang, Ya-Ge; Chen, Hao-Wei; Zhang, Hong-Xin; Wang, Ke; Su, Jie; Chen, Yan-Ru; Wang, Xiang-Ru; Fu, Zhen-Fang; Cui, Min (Frontiers in Microbiology, 2022)
The establishment of Japanese encephalitis virus (JEV) infection in brain microvascular endothelial cells (BMECs) is thought to be a critical step to bring about viral encephalitis with compromised blood-brain barrier (BBB), of which the mechanisms are not completely understood. In this study, we found that epidermal growth factor receptor (EGFR) is related to JEV escape from interferon related host innate immunity based on a STRING analysis of JEV infected primary human brain microvascular endothelial cells (hBMECs) and mouse brain. At the early phase of the infection processes, JEV induced the phosphorylation of EGFR. In JEV infected hBMECs, a rapid internalized EGFR that colocalizes with the endosomal marker EEA1 occurred. Using specific inhibitors to block EGFR, the reduced production of viral particles was observed. Similar results were also found in an EGFR-KO hBMEC cell line. Even though the process of viral infection in attachment and entry was not noticeably influenced, the induction of IFNs in EGFR-KO hBMECs was significantly raised, which may account for the decreased viral production. Further investigation demonstrated that EGFR downstream cascade ERK, but not STAT3, was involved in the antiviral effect of IFNs, and lowered viral yield was observed by utilizing the specific inhibitor of ERK. Taken together, the results revealed that JEV induces EGFR activation, leading to suppression of interferon signaling, and promoting viral replication, which could provide a potential target for future therapies for the JEV infection.